THE PATTERN OF E-BOOK USE AMONGST UNDERGRADUATES IN MALAYSIA: A CASE OF TO KNOW IS TO USE - Ismail, Roesnita; A.N., Zainab (Malaysian Journal of Library and Information Science, 2005)
This exploratory study focuses on identifying the usage pattern of e-books especially on how, when, where and why undergraduates at the Faculty of Computer Science and Information Technology (FCSIT), University of Malaya (UM), Kuala Lumpur use or do not use the e-books service provided by the University of Malaya library. A total of 206 (82%) useable questionnaires form the basis of analysis. The results indicate even though the students are heavy users of the Internet, rate themselves as skilled in Internet use and have positive attitude towards the e-book service, the level of e-book use is still low (39%). The students become aware of the e-book service mainly while visiting the University of Malaya Library Website, or are referred to it by their lecturers, friends or the librarians. About 70% rate positively on the e-book service. Those who are users of e-books find e-books easy to use and their usages are mainly for writing assignment or project work. Most respondents prefer to use e-versions of textbooks and reference sources. Generally, both users and non-users of e-books prefer to use the printed version of textbooks especially if the text is continuously used. There are significant difference between the frequency of e-book use and gender; between past usage of e-book and preference for electronic textbooks and reference books. The possible factors which may be related to e-book use are categorized into 4 groups and presented in a model, which comprises the ICT competencies of the students, their cognitive makeup, the degree of user access to the e-books and the functional or use factors.